2022
DOI: 10.1186/s12889-022-12498-1
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic factors associated with suicidal behaviors in South Korea: systematic review on the current state of evidence

Abstract: Background The economic and human costs of suicide to individuals, families, communities, and society make suicide a major public health problem around the world. Suicide rates in South Korea are among the highest in the world. This paper is the first systematic review investigating socioeconomic risk factors for suicidal behaviors (suicidal ideation, attempted suicides, and completed suicides) in South Korea. Methods We performed a systematic revi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 80 publications
1
15
2
Order By: Relevance
“…Although suicide rates vary from country to country, suicide among older adults is a global public health issue, as they commit suicide at higher rates than other age groups [ 3 , 4 ]. Notably, South Korea’s suicide rate has ranked high among Organization for Economic Co-operation and Development (OECD) countries for over ten years [ 5 , 6 ]. In 2020, the suicide rate among older adults was 41.7 per 100,000 people in South Korea [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although suicide rates vary from country to country, suicide among older adults is a global public health issue, as they commit suicide at higher rates than other age groups [ 3 , 4 ]. Notably, South Korea’s suicide rate has ranked high among Organization for Economic Co-operation and Development (OECD) countries for over ten years [ 5 , 6 ]. In 2020, the suicide rate among older adults was 41.7 per 100,000 people in South Korea [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a significant correlation in which suicidal thoughts become stronger as financial difficulties increase [45]. As economic difficulties are common stressors for suicide deaths, it is necessary to establish a stronger social safety net for vulnerable groups to cope with Korea's socioeconomic polarization and welfare blind spots [46,47]. Quantitative analysis, such as statistical data alone, makes it difficult to grasp the risk factors for suicide and the personal meaning of people who took their own life.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the focus of this study was limited to PPC. Some studies have suggested that other family factors, such as parental warmth ( Li et al, 2016 ) and family socioeconomic status ( Raschke et al, 2022 ), might be strongly associated with suicide risk. Future studies should also consider these variables.…”
Section: Discussionmentioning
confidence: 99%